Biohydrogen production and storage from depleted hydrocarbon reservoirs: A review of the strategies to improve biohydrogen production for sustainable energy transition - Abutu, David; Wan Mohd Hafizuddin, Wan Yussof; Nwaichi, Peter Ikechukwu; Umunnawuike, Chika; Nyah, Francis; Money, Barima; Agi, Augustine Aja (Elsevier B.V., 2025)
Hydrocarbon reservoirs are a rich source of carbon hosting various microorganisms. Many of these reservoirs have reached the late stage of their production, however, a sizeable amount of the initial oil in place is still left unrecovered at abandonment. These depleted reservoirs contain a significant amount of organic matter in the form of residual oil which can be exploited for hydrogen production. Therefore, the objective of this research is to provide a comprehensive review of the strategies to improve hydrogen production from depleted hydrocarbon reservoirs for sustainable energy transition. Herein the different pathways of hydrogen production from depleted hydrocarbon reservoirs were discussed. Likewise, the factors affecting hydrogen production were identified and elucidated. Furthermore, strategies to improve hydrogen production were presented. Also, field applications were reviewed. Finally, the challenges to be encountered during hydrogen production that might hinder the successful energy transition have brought to light novel concepts for research which are highlighted herewith proffered technical solutions. Laboratory studies have shown that hydrogen production from hydrocarbon reservoirs can be enhanced using innovative strategies that incorporate bacteria and immobilization, surfactants, nanoparticles, nutrient injection and gene manipulation. Thus, it can be concluded that with proper optimization strategies, biohydrogen production from depleted reservoirs could significantly contribute to meeting energy demands while reducing carbon emissions and repurposing unused hydrocarbon assets.